Real-world effectiveness and safety of direct-acting antivirals for the treatment of hepatitis C virus in kidney and liver transplant recipients: experience of a large transplant center in Brazil - Pacheco, Larissa Sgaria; Ventura, Pedro Enrico; Kist, Roger; Garcia, Valter Duro; Meinerz, Gisele; Tovo, Cristiane Valle; Cantisani, Guido Pio Cracco; Zanotelli, Maria Lucia; Mucenic, Marcos; Keitel, Elizete (Revista do Instituto de Medicina Tropical de São Paulo, 2023)
Direct-acting antivirals are the gold-standard treatment for chronic HCV infections, but few studies have investigated their use on kidney and liver transplant recipients. We conducted a real-world study to evaluate the rates of sustained virological response with direct-acting antivirals in kidney and liver transplant recipients. Moreover, it also aimed to evaluate direct-acting antivirals (DAAs) interference with immunosuppressant levels and to describe the frequency of adverse events. As part of this retrospective observational cohort, we included adult patients that had undergone a kidney transplant (KT) or liver transplant (LT) at our center, had a chronic HCV infection, and were treated with DAAs from June 2016 to December 2021. A total of 165 patients were included in the analysis, divided in 108 KT and 57 LT recipients. HCV genotype 1 was more frequent in KT (58.4%), and genotype 3 was more prevalent in LT (57.9%) patients. Sustained virological response was achieved in 89.6% of patients. Adverse effects were reported by 36% of patients. There were significant interactions with immunosuppressants requiring dose adjustments. A total of three episodes of rejection were reported in KT recipients. In conclusion, DAA treatment resulted in high rates of SVR and was well tolerated in both kidney and liver transplant patients. Adverse events were frequent but not severe in most patients, with low treatment drop-out rates. Interactions with immunosuppressants need monitoring since dose adjustments may be required. Reporting real-life experiences is important to help build evidence for patient management in non-controlled environments.